THE INFLUENCE OF AUTHORITARIAN LEADERSHIP STYLE, JOB STRESS AND WORKLOAD ON COUNTERPRODUCTIVE WORK BEHAVIOR OF PT EMPLOYEES. SOCFINDO, MEDAN CITY - Riska Maharani Damanik; Yanita; A. Hadi Arifin; Sullaida; Yusniar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
Counterproductive work behavior is a common phenomenon that poses challenges in human resources. In June 2022, employees at PT. Socfindo in North Sumatra, Medan, initiated a strike action. The cause of this strike was related to deductions in premiums, bonuses, and other benefits. While employees traditionally received bonuses every four months, a reduction began in 2021, resulting in employees only receiving bonuses for three months. Consequently, the increased workload and heightened work stress at PT. Socfindo were attributed to an authoritarian leadership style, contributing to employees' counterproductive work behavior. This study aims to investigate the relationships between authoritarian leadership style, workload, work stress, and counterproductive work behavior. A quantitative approach was employed, involving the distribution of questionnaires to 65 respondents which is employed at PT. Socfindo located in Medan city. Primary data collection utilized questionnaires, and the analysis was performed through multiple linear regression using SPSS 23. The findings indicate that the work stress variable has a positive impact on counterproductive work behavior. Furthermore, both work stress and workload exhibit a negative influence on employees' counterproductive work behavior.